Comparative Analysis of Activities of Carica Papaya.Leafe Extract and some Conventional Antibiotic Against Salomonella and Shigella SPP.Isolated In Fish pond in Ile-Ife - Emoitologa, Progress Afegbai (Obafemi Awolowo University, 2023)
xviii,134